MOTIVASI KEBUTUHAN MASLOW PADA TOKOH DALAM NOVEL BEKISAR MERAH KARYA AHMAD TOHARI - Astri Agnisa; Syafrial Syafrial; Hadi Rumadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This study aims to describe the motivation of Maslow's needs for characters in the Bekisar Merah novel by Ahmad Tohari. This study used descriptive qualitative method. Data obtained using documentation techniques. Then, the data is analyzed using description analysis techniques. This technique is done by describing the facts then followed by elaborating to the stage of providing understanding and explanation. From the data obtained, in Ahmad Tohari's Bekisar Merah novel, four Maslow's needs were motivated by figures. The four needs are physiological needs, security needs, love needs, and need for appreciation. While the need for self-actualization cannot be found because all figures do not succeed in meeting their previous needs. The characters in this novel move more on the structure of the personality of the id because the actions of the characters motivated by the need for security and the most found physiological needs. In terms of intrinsic elements, the setting of the scene provides the most motivation for meeting Maslow's needs and the style of language widely used in meeting the needs of the award.Key Words: Motivation for Maslow's Needs, Character, Bekisar Merah